(untitled) (Conferencea, 2024)
Malocclusion is a problem that affects 70% of the world’s population. Both conservative and surgical methods are used to correct this defect. Modern orthodontics has a lot of opportunities for non-surgical restoration of the aesthetics of the dentition, the most common and effective structures are aligners. This analysis presents the frequency of use of dental aligners, which have a great influence on the formation of the dental system of the patient. The data presented in the article can be useful for the development of preventive and therapeutic measures, in the prognosis and management of children with this pathology in an individual and family perspective.